2018
DOI: 10.1093/bioinformatics/bty186
|View full text |Cite
|
Sign up to set email alerts
|

pyNBS: a Python implementation for network-based stratification of tumor mutations

Abstract: The package, along with examples and data, can be downloaded and installed from the URL https://github.com/idekerlab/pyNBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Identification of tumor subclasses based on somatic non-synonymous mutations was performed using oncosign (v1.0) (Ciriello et al, 2013) and Network-Based Stratification (pyNBS, downloaded on 4th June 2020) (Hofree et al, 2013; Huang et al, 2018). Significantly mutated genes identified using MutsigCV (Lawrence et al, 2013), as well as genes identified as significantly mutated in HCC in at least 2 of Martincorena et al(Martincorena et al, 2018), Schultz et al (Schulze et al, 2015), Fujimoto et al (Fujimoto et al, 2016), Bailey et al (Bailey et al, 2018) (excluding TERT ) and mutated (non-synonymous) in at least 3 tumor samples were included for the clustering.…”
Section: Star Methodsmentioning
confidence: 99%
“…Identification of tumor subclasses based on somatic non-synonymous mutations was performed using oncosign (v1.0) (Ciriello et al, 2013) and Network-Based Stratification (pyNBS, downloaded on 4th June 2020) (Hofree et al, 2013; Huang et al, 2018). Significantly mutated genes identified using MutsigCV (Lawrence et al, 2013), as well as genes identified as significantly mutated in HCC in at least 2 of Martincorena et al(Martincorena et al, 2018), Schultz et al (Schulze et al, 2015), Fujimoto et al (Fujimoto et al, 2016), Bailey et al (Bailey et al, 2018) (excluding TERT ) and mutated (non-synonymous) in at least 3 tumor samples were included for the clustering.…”
Section: Star Methodsmentioning
confidence: 99%
“…If the pathway is not enriched, 0 is inserted into that entry. We used this matrix for implementing the non negative matrix factorization without a network regularizer and then consensus clustering from pyNBS package which is a Python implementation of NBS [65]. The identified groups were searched for if any identified spatial patch tends to represent a group using hypergeometric testing.…”
Section: Methodsmentioning
confidence: 99%
“…Smooth mutations over a gene interaction network. The gene-gene interaction network used in this example contains high-confidence cancer-specific interactions 18 . This specific network effectively clusters tumour samples of patients, distinguishing them by tumour type and time of survival.…”
Section: Use Casesmentioning
confidence: 99%
“…genoFile <-paste(system.file("extdata",package="netDx"), "TGCT_mutSmooth_geno.txt",sep=getFileSep()) geno <-read.delim(genoFile,sep="\t",header=TRUE,as.is=TRUE) phenoFile <-paste(system.file("extdata",package="netDx"), "TGCT_mutSmooth_pheno.txt",sep=getFileSep()) pheno <-read.delim(phenoFile,sep="\t",header=TRUE,as.is=TRUE) rownames(pheno) <-pheno$ID Smooth mutations over a gene interaction network. The gene-gene interaction network used in this example contains high-confidence cancer-specific interactions 18 . This specific network effectively clusters tumour samples of patients, distinguishing them by tumour type and time of survival.…”
Section: Path_grlistmentioning
confidence: 99%